Binding and metabolism of platelet-activating factor by human neutrophils. - J T O'Flaherty; J R Surles; J Redman; D Jacobson; C Piantadosi; R L Wykle (The Journal of Clinical Investigation, 1986)
Human polymorphonuclear neutrophils rapidly incorporated radiolabeled platelet-activating factor, 1-O-[hexadecyl-9, 10-3H2]-2-acetyl-sn-glycero-3-phosphocholine ([3H]PAF), and then metabolized it into its sn-2-fatty acyl derivative. Fractionation of radiolabel-pretreated cells over Percoll gradients revealed that virtually all of the intact [3H]PAF was located in nongranule membranes that were enriched with alkaline phosphatase and cell surface glycoproteins. While still membrane associated, the ligand was rapidly converted to its acyl derivative and then more slowly transferred to specific granules and, to a lesser extent, azurophilic granules. In contrast, neutrophils did not metabolize [3H]PAF at 4 degrees C but rather gradually accumulated it in their alkaline phosphatase-enriched membrane subfractions. These same subfractions contained receptors for the ligand, as determined by their capacity to bind [3H]PAF specifically. Binding was readily saturated, partially reversible, and fit a two receptor model; dissociation constant (Kd) values for high and low affinity sites were 0.2 and 500 nM, respectively. Receptors with similar affinities were detected in whole cells. Furthermore, the potencies of several structural analogues in inhibiting binding of [3H]PAF to membranes correlated closely with their respective potencies in stimulating degranulation responses. Finally, quantitative studies suggested all or most of the cell's receptors were membrane associated. We conclude that PAF rapidly enters cellular membranes to bind with specific receptors that trigger function. The intramembranous ligand is also deacetylated, acylated, and then transferred to granules. This metabolism may be sufficiently rapid to limit ligand-receptor binding and distort quantitative analyses of receptors.